The contributions of social movement Nós Podemos Paraná (We Can, Paraná) for the creation and sharing of knowledge - Drago, Isabela (2014)
This paper is a descriptive research about the contributions of the movement Nós Podemos Paraná (We Can, Paraná) for the creation and sharing of knowledge. From documentary survey, the methodology of the Movement,the role and the importance of each of its structures are described: Core Articulator, Dialog’s Circles, Knowledge’s Circles, Core Workplaces and Projects Group. Analyzes Dialog’s circle and Knowledge’s Circles in addition of the constitution and characteristics of Cores Workplaces, pointing out the barriers to knowledge sharing and their potential as a community of practice. Concludes that the studied core can be considered as a community of practice, in maturity phase and its members commit themselves, creating and developing common projects, renewing interests, commitment and relationship, and for their positive results , turning the project into a regional reference.